1991
DOI: 10.1002/anie.199100991
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic and Stoichiometric Enantioselective Addition of Diethylzinc to Aldehydes Using a Novel Chiral Spirotitanate

Abstract: Simple variation of the reaction conditions in the addition of Et2Zn to aldehydes in the presence of spirotitanate 1 can lead to a reversal in the configuration of the product. Stoichiometric amounts of the spirotitanate result in Re addition of Et2Zn to the aldehyde (up to 98% ee). In the presence of equimolar amounts of Ti(OCHMe2)4, catalytic amounts of 1 lead to Si addition of Et2Zn (up to 99% ee).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(23 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…The reaction was also tested with aliphatic aldehydes (entries [17][18][19][20][21][22]. In general, we observed that aliphatic aldehydes reacted more efficiently providing the corresponding alcohols with better yields and ees than the aromatic ones.…”
Section: Asymmetric Addition Of Diethylzinc To Aldehydesmentioning
confidence: 97%
“…The reaction was also tested with aliphatic aldehydes (entries [17][18][19][20][21][22]. In general, we observed that aliphatic aldehydes reacted more efficiently providing the corresponding alcohols with better yields and ees than the aromatic ones.…”
Section: Asymmetric Addition Of Diethylzinc To Aldehydesmentioning
confidence: 97%
“…Since 1986, when DAIB was introduced by Noyori, 1 the amount of very useful and efficient dialkylamino alcohols has grown dramatically, 2 and now includes not only dialkylamino alcohols but also amino thiols, 3 oxazolines 4-6 and even diols such as TADDOLs 7,8 and BINOLs. [9][10][11] Further progress in enantioselective additions to aldehydes was achieved, when Ohno and co-workers reported diethylzinc additions in the presence of titanium tetraisopropoxide and a chiral bissulfonamide.…”
Section: Introductionmentioning
confidence: 99%
“…24 Besides the extensive work on the catalytic asymmetric ZnEt 2 addition to aldehydes, recent years have seen rapid growth in the study of the addition of functional organozincs such as arylzincs, 57 vinylzincs, 811 and alkynylzincs 1215 to carbonyl compounds. These reactions can produce a variety of functional chiral alcohols that are important in organic syntheses.…”
Section: Introductionmentioning
confidence: 99%